The cicada fauna of Pakistan including the description of four new species (Hemiptera: Cicadoidea: Cicadidae) - Ahmed, Zubair; Sanborn, Allen F. (Zootaxa, 2010)
The first faunal analysis of the cicadas of Pakistan is provided. Field work and museum study has added significantly to the known cicada fauna of Pakistan. Literature records provide evidence for 18 species inhabiting what is currently Pakistan. The first records of Platypleura basialba (Walker), Platypleura mackinnoni Distant, Cicadatra persica Kirkaldy, Cicadatra xantes (Walker), Meimuna velitaris (Distant), Haphsa nicomache (Walker), and Paharia putoni (Distant) are provided. Psalmocharias balochii sp. n., Psalmocharias chitralensis sp. n., Psalmocharias gizarensis sp. n. and Psalmocharias japokensis sp. n. are described as new. These are the first records of members of the genera Meimuna Distant and Haphsa Distant in Pakistan. The new records and new species represent a 61% increase in faunal diversity. The cicada fauna of Pakistan now comprises of a total of 29 species from 13 genera, five tribes and three subfamilies. These data provide a more accurate understanding of cicada diversity at the junction of the Oriental and Palaearctic regions.